DAMPAK PANDEMI COVID-19 BAGI PEMASARAN UMKM SYARIAH DI INDONESIA - Delia Dwiyanti Hasanah; Siti Rosiyana Dewi; Anya Aurellya; Selva Selfia Ginanjar; Nadya Az-Zahra; Popon Srisusilawati (Master of Management, Mataram University, 2022)
The existence of Covid-19 has presented various kinds of problems, including problems that have occurred in marketing in Indonesia. The Covid-19 pandemic may be viewed by some business actors as a disaster, but if we are smart in managing or managing a business by looking at the situation and by understanding changes in consumer behavior, we will be able to boost sales even in the midst of this pandemic. The impact that occurred on offline sellers was that on average, micro, small and medium enterprises felt a decline in turnover during the Covid-19 presence. however, several micro, small and medium enterprises remained stable and experienced increased sales due to these increased efforts. Adjusting products and developing several strategies to survive, online sales are not much different from offline sales, in online marketing there has also been a decline and increase,E-commerce has played a role in the Indonesian economy during the Covid-19 pandemic for businesses, consumers and the government. . For business actors, e-commerce is a solution to overcome the impact of Covid-19 to increase business scale because many investors are investing in this field. The reason people choose to buy in online sales is because it is safer and more effective when making online transactions. The reason is because it is done without physical contact and continues to carry out health protocols. Keywords: Covid-19, e-commerce, SMeS, marketing